Exploring botanical diversity, ecological traits, and edaphic determinants in Kala Chitta National Park, Pakistan: Implications for conservation and management - Muhammad Waheed; Um e Hani; Fahim Arshad; Asma Jabeen; Saud Alamri; Manzer H. Siddiqui; Shiekh Marifatul Haq; Muhammad Shoaib; Rainer W. Bussmann (Environmental and Sustainability Indicators)
Globally, environmental degradation has prompted several countries to strengthen their protected area networks to halt biodiversity loss. National parks incorporate into their design, are based on scientific evidence, and offer a complete management mechanism to enable successful conservation for the most ecologically critical and vulnerable ecosystem. However, managing these protected areas effectively requires a grasp of the complex dynamics of plant ecosystems and edaphic factors. Nevertheless, Pakistan's protected areas have seen the least investigation of these relationships. To fill this knowledge gap, this study investigates the vegetation dynamics and edaphic factors that influence plant distribution in Kala Chitta National Park of Pakistan. A comprehensive botanical survey documented 203 plant species across 60 study sites, revealing a diverse flora comprising species from 160 genera and 54 families. The most abundant families were Poaceae (34 species) and Fabaceae (21 species), Amaranthaceae (13 species) and Asteraceae (15 species). The majority of species were herbaceous (49.2%), followed by grasses (16.7%) and shrubs (15.2%). Climbers and ferns constituted 1.4% and 1.9% of the total, respectively, with co-dominant habits of tall reed and sedge accounting for 2.9% of the vegetation. Ecologically, Therophytes emerged as the most numerous life forms (42.8%), followed by hemicryptophytes (17.7%) and megaphanerophytes (8.3%). Analysis of leaf spectra revealed Nanophylls as the dominant type (36.9%), followed by Microphylls (33%). Phytogeographical distribution highlighted three major clusters, with Asia Tropical, Asia Temperate, and Europe accounting for 45% of species. Four distinct plant communities were identified using TWINSPAN analysis: Senegalia-Dichanthium-Justica (SDJ), Neltuma-Lantana-Cannabis (NLC), Prosopis-Saccharum-Desmostachya (PSD), and Dodonaea-Alhagi-Oxalis (DAO). Each community exhibited unique species compositions and ecological gradients influenced by edaphic factors. PCA revealed associations between specific edaphic variables and plant communities, with available phosphorus (AP) and potassium (AK) linked to the NLC community. At the same time, total nitrogen (TN) was predominantly associated with the DAO community. These findings highlight the importance of soil conservation and sustainable land management practices for preserving biodiversity and ecosystem integrity within Kala Chitta National Park. Future research should focus on long-term monitoring of vegetation dynamics and collaborative conservation initiatives involving local stakeholders to promote ecosystem resilience in the face of environmental change.